ROLE OF ETIOLOGICAL FACTORS IN THE DEVELOPMENT OF CHRONIC GASTRITIS AND STOMACH CANCER IN RESIDENTS OF A LARGE INDUSTRIAL CENTER OF WESTERN SIBERIA - Красильникова, Полина Леонидовна; Филимонов, Сергей Николаевич; Плотникова, Екатерина Юрьевна (Medicine in Kuzbass, 2019)
Subject of the study. Social and phenotypic factors affecting the severity of inflammatory and oncologic proliferative changes of the gastric mucosa (GM) in the residents of a large industrial center of Western Siberia.Objective – the purpose was studying the state of the gastric mucosa in practically healthy people, the subjects with gastritis and stomach cancer depending on gender, anthropometric indices, age, eating behavior, adherence to bad habits, Helicobacter pylori infection.Material and methods. 201 individuals with chronic gastritis, stomach cancer and healthy subjects were examined. Gender and age were studied, body mass index was calculated. The following questionnaires were used: AUDIT on alcohol abuse and eating behavior based on the European sample EPIC, which revealed food adherence. We studied the dependence on tobacco smoking, Helicobacter pylori infection. All patients underwent fibrogastroduodenoscopy with vital biopsy sampling and the subsequent histological verification.Main results. Among the etiological factors studied, a number of predictors of malignant transformation in the gastric mucosa was determined both in practically healthy residents of the region and in the patients with already developed inflammation. A direct relationship has been established between the risk of malignancy and the patient’s age, alcohol abuse and adherence in the diet to roasted meat. No statistically significant factors leading to the development of the inflammatory GM process were found in this study.Conclusion. The development of the oncologic proliferative process in GM in the residents of a large industrial center in Western Siberia is directly related to the peculiarities of nutrition, adherence to alcohol, and age of the subjects surveyed.
Keywords: chronic gastritis; Helicobacter pylori; stomach cancer; etiological factors